"I've Been a Long Time Leaving": The Role of Limited Skill Transferability in Increasing Suicide‐Related Cognitions and Behavior in Veterinarians. Issue 3 (12th July 2016) - Crane, Monique F.; Phillips, Jacqueline K.; Karin, Eyal
Abstract : Barriers to occupational mobility were investigated to determine whether they increased reported suicide‐related cognitions and behavior over 12 months. This was explored in a two‐wave longitudinal study. Intention to leave, depression, perceived skill transferability, and suicide‐related cognitions and behavior was measured at both time points approximately 12 months apart. Results indicated that when there was a high intention to leave at T1, reported suicide‐related cognitions and behavior increased over 12 months only when skill transferability to other professions was perceived to be limited. Findings support the role of limited occupational mobility in suicide‐related cognitions and behavior.